Uptake of human papillomavirus (HPV) vaccination in Hong Kong: Facilitators and barriers among adolescent girls and their parents - Yuen, Winnie Wing Yan (PLoS One, 2018)
The present study is aimed at assessing the feasibility of delivering the HPV (human papillomavirus) vaccine to girls through a school-based program in Hong Kong, as well as to examine the facilitators and barriers associated with their participation. We approached 1,229 eligible girls aged 9 to 14 at eight schools in Hong Kong to join the program and then delivered the bivalent HPV vaccine at 0 and 6 months over the course of one school year. The students and their parents completed separate questionnaires to indicate their decision on whether or not to participate, and to assess their knowledge of cervical cancer and the HPV vaccine. The overall vaccine uptake was 81.4% (1,000/1,229) for the first dose and 80.8% (993/1,229) for the second dose. Parents and students were given separate questionnaires and asked whether or not they would like to participate in the vaccination program. 87.1% (1,010/1,160) of parents and 84.9% (974/1,147) of students indicated that they would join the program. The reasons associated with parents’ decision not to vaccinate their daughters primarily included concerns around side effects and safety. Multivariate regression analysis showed that parents who thought that the vaccine would protect their daughter from getting cervical cancer (OR = 3.16, 95% CI = 1.39–7.15, p < .01), and those who reported having a doctor’s recommendation (OR = 4.54, 95% CI = 1.05–19.57, p < .05) were more likely to join the program. In contrast, parents who had never heard of the vaccine (OR = .15, 95% CI = .03–.71, p < .02), those who were willing to pay more than HK$2,000 for the vaccine (OR = .39, 95% CI = .19–.81, p < .05), or had a preference to access it through a private clinic (OR = .44, 95% CI = .26–.75, p < .01) were significantly less likely to allow their daughter to join the program. Delivery of the HPV vaccine with high uptake rate in a school setting is feasible in Hong Kong. Engaging key stakeholders including school administrators, teachers and community physicians, and providing relevant information on safety and vaccine effectiveness to parents were important to the success of the program.